The Influence of Transformational Leadership, Motivation and Work Environment on Employee Performance Mediated by Discipline Work at PT. Pupuk Indonesia Pangan - Kurniawan*, Iqbal; Khurniawan, Arie Wibowo; Mubarok, Faizul (Universitas Syiah Kuala, 2024)
Problems that occur at PT. Pupuk Indonesia Pangan where there are allegations of problems that cause the company's revenue targets to not be achieved from year to year, which has an impact on the company's revenue achievement, which is caused by employee performance always decreasing every year. In theory, many factors can influence employee performance, including transformational leadership, motivation and work environment and work discipline. Performance is various forms of results achieved by each individual in their field of work. The purpose of this research is to determine the influence of transformational leadership, motivation and work environment on employee performance as mediated by work discipline at PT. Pupuk Indonesia Pangan with a population of 110. The sample used was 110 respondents. Variable measurement was carried out using a Likert scale. Data analysis was carried out using SmartPLS. From the results, there is a significant positive direct effect of transformational leadership, motivation and environment on work discipline. There is a significant positive direct effect of motivation and work discipline on employee performance, while transformational leadership and the work environment have no effect on employee performance. Work discipline is able to mediate transformational leadership, motivation and work environment on employee performance at PT. Pupuk Indonesia Pangan. It can be concluded that both directly and indirectly there is an influence of transformational leadership, motivation and work environment on employee performance which is mediated by work discipline at PT. Pupuk Indonesia Pangan.